Workload on Service Performance Through Work Life Balance and Work Capability - Saldin Paputungan; Lucky O. H. Dotulong; Rita N. Taroreh; Genita G. Lumintang (Jurnal Manajemen, 2025)
This study investigates the impact of workload on service performance while considering other influencing factors. Using a causal research design with a quantitative approach, data were gathered through questionnaires distributed to 100 employees of RSUD Sayang Rakyat Makassar. Analysis was conducted with the Structural Equation Model (SEM) using PLS. The results show that workload has a positive and significant influence on service performance through workability. A higher workload motivates employees to develop skills, enhancing service outcomes. These findings align with motivation and competency theories, which emphasize that improving employee skills can boost productivity and service quality. The study contributes to management science by showing that effective workload management enhances employability and service performance. Organizations are advised to implement workload strategies and support skill development. Limitations include the use of cross-sectional data and a focus on a single industry, suggesting that future research should broaden the generalizability.